Exploring Non‐Coding RNAs in RNAcentral. Issue 1 (26th August 2020) - Sweeney, Blake A.; Tagmazian, Arina A.; Ribas, Carlos E.; Finn, Robert D.; Bateman, Alex; Petrov, Anton I.
Abstract: Non‐coding RNAs are essential for all life and carry out a wide range of functions. Information about these molecules is distributed across dozens of specialized resources. RNAcentral is a database of non‐coding RNA sequences that provides a unified access point to non‐coding RNA annotations from >40 member databases and helps provide insight into the function of these RNAs. This article describes different ways of accessing the data, including searching the website and retrieving the data programmatically over web APIs and a public database. We also demonstrate an example Galaxy workflow for using RNAcentral for RNA‐seq differential expression analysis. RNAcentral is available at https://rnacentral.org . © 2020 The Authors. Basic Protocol 1 : Viewing RNAcentral sequence reports Basic Protocol 2 : Using RNAcentral text search to explore ncRNA sequences Basic Protocol 3 : Using RNAcentral sequence search Basic Protocol 4 : Using RNAcentral FTP archive Support Protocol 1 : Using web APIs for programmatic data access Support Protocol 2 : Using public Postgres database to export large datasets Support Protocol 3 : Analyze non‐coding RNA in RNA‐seq datasets using RNAcentral and Galaxy